6.TREATMENT OUTCOME OF ATYPICAL FEMORAL FRACTURES (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to evaluate the results of treatment of atypical femoral fractures to provide information for clinical practice.Subjects and methods: Retrospective from August 2021 to August 2024, including patients diagnosed with atypical femoral fractures and surgery. Patients are diagnosed if they have at least 4 out of 5 criteria: mild trauma, transverse fracture, complete or incomplete fracture, minimal comminution, thickening of the lateral cortical bone. Exclusion criteria included bone fractures due to the tumor, severe systemic illness, and refusal to participate in the study.Patient demographics, medication history, and fracture characteristics were recorded. Postoperative outcomes were assessed using X-rays at 3 months, 6 months and at the final follow-up visit. Functional outcomes were measured using the CAS score.Results: The study included 27 atypical femoral fractures in 26 patients, with a follow-up of 10.7 months. Most patients were women (96.1%), with an average age of 69.3 years. A significant portion (73.1%) used alendronate. Fractures were located in the upper and middle third of the femur. 18 of 20 patients followed for at least 6 months achieved complete bone healing, with an average healing time of 8.1 months. Complications included 1 case of intramedullary nail breakage, 1 infection, and 2 non-unions.Discussion: The study found that AFF predominantly affects older women, and related to prolonged Bisphosphonate use, particularly alendronate, is significant, and prolonged use increases fracture risk. Diagnostic imaging revealed specific fracture patterns and cortical thickening. Intramedullary nailing shown better healing times compared to plating. Functional recovery, assessed using CAS, indicated most patients regained satisfactory ambulation ability.Conclusions: Atypical femoral fractures primarily affects elderly women with a history of Bisphosphonate use. Rehabilitation according to the CAS score is good. More attention needs to be paid to surgical technique to ensure bone union because the rate of non-union is high.
Keywords: Atypical femoral fracture; Bisphosphonate; lateral cortex thickening